2012
DOI: 10.3174/ajnr.a3245
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Imaging of the Congenitally Thickened Corpus Callosum

Abstract: SUMMARY:This report presents 4 subjects with congenital segmental callosal thickening, an uncommon malformation studied with MR imaging and DTI. Medical records were reviewed for genetic testing and neurodevelopmental status. Three subjects had profound developmental delay; 3 had seizures. MR imaging showed segmental thickening of the rostral and/or midcallosal body. Associated anomalies included polymicrogyria in 1 patient and optic hypoplasia in 1. DTI showed that the segmental thickening was due to anomalou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Diffusion tractography has been shown to be helpful in distinguishing the white matter connections within the corpus callosum, such as the presence of homo-or heterotopic fiber tracts. 36,37 This was a retrospective study with resultant limitations inherently present. We cannot infer the incidence of olfactory anomalies in the pediatric population.…”
Section: 29mentioning
confidence: 99%
“…Diffusion tractography has been shown to be helpful in distinguishing the white matter connections within the corpus callosum, such as the presence of homo-or heterotopic fiber tracts. 36,37 This was a retrospective study with resultant limitations inherently present. We cannot infer the incidence of olfactory anomalies in the pediatric population.…”
Section: 29mentioning
confidence: 99%
“…This particular bundle has been described in association with thickened corpus callosum [3,17] but also in patients with no thickened corpus callosum [30]. Transitory corpus callosum axons have been described during development [27].…”
Section: Discussionmentioning
confidence: 97%
“…However no DTI metrics of thickened corpus callosum have been reported. Two recent papers reported that DTI and fiber tract reconstruction can show anomalous longitudinal supracallosal fibers separated from the cingulum in congenital cases of thickened corpus callosum [3,17]. One case was also analyzed histologically [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In partial callosal agenesis anomalous supracallosal longitudinal WM bundles were studied by Q-Ball imaging [13]. More recently, Rollins [14] reported four patients with SLB, studied with DTI, and hypothesized these fibers might represent heterotopic cingulum, induseum griseum or aberrant callosal axons. No quantitative measurements were performed and fornix was not reconstructed.…”
Section: Discussionmentioning
confidence: 99%